Right inferior prefrontal cortex mediates response inhibition while mesial prefrontal cortex is responsible for error detection - Rubia, Katya; Smith, Anna B; Brammer, Michael J; Taylor, Eric (NeuroImage (Orlando, Fla.), 2003)
Inhibitory control and error detection are among the highest evolved human self-monitoring functions. Attempts in functional neuroimaging to effectively isolate inhibitory motor control from other cognitive functions have met with limited success. Different brain regions in inferior, mesial, and dorsolateral prefrontal cortices and parietal and temporal lobes have been related to inhibitory control in go/no-go and stop tasks. The widespread activation reflects the fact that the designs used so far have comeasured additional noninhibitory cognitive functions such as selective attention, response competition, decision making, target detection, and inhibition failure. Here we use rapid, mixed trial, event-related functional magnetic resonance imaging to correlate brain activation with an extremely difficult situation of inhibitory control in a challenging stop task that controls for noninhibitory functions. The difficulty of the stop task, requiring withholding of a triggered motor response, was assured by an algorithm that adjusted the task individually so that each subject only succeeded on half of all stop trials, failing on the other half. This design allowed to elegantly separate brain activation related to successful motor response inhibition and to inhibition failure or error detection. Brain activation correlating with successful inhibitory control in 20 healthy volunteers could be isolated in right inferior prefrontal cortex. Failure to inhibit was associated with activation in mesial frontopolar and bilateral inferior parietal cortices, presumably reflecting an attention network for error detection.